2022
DOI: 10.1002/app.53208
|View full text |Cite
|
Sign up to set email alerts
|

Novel functional material incorporating flexirubin‐type pigment in polyvinyl alcohol_kefiran/polycaprolactone nanofibers

Abstract: In this study, needleless electrospinning technology was used to obtain flexirubin (F)‐loaded polyvinyl alcohol (PVA)_kefiran (KF)/polycaprolactone (PCL) electrospun nanofibers. The SEM images of PVA_KF_ F and PCL_F nanofibers displayed beadless morphology with average diameters of 211.90 ± 96.08 and 1610.71 ± 996.68 nm, respectively. FTIR‐ATR analysis revealed increased intensity at specific wavelengths, after pigment incorporation. The high porosity exhibited by each layer and the mechanical properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…PCL sample shows a rough and compact surface, characteristic of tough materials while the inclusion of 0.1% wt of LWP induces a slight increase in roughness compared to the matrix, probably due to the presence of the nanometric pigment which in small quantities works as a concentrator of internal stresses. When the LWP content is increased to 1% wt, the surface becomes less jagged and the roughness decreases suggesting that LWP favors internal creep as a sort of plasticizer. , The fractured surface of PBS appears rough and segmented with the typical morphology of a rigid and tough material, whereas the PBS_0.1LWP sample takes on a less-wrinkled appearance, indicating a less tenacious behavior; with 1% wt of LWP in PBS, the fracture shows an evident reduction of the roughness, suggesting a more rigid and brittle behavior at break of the material. Unlike PCL-based samples, in PBS the pigment seems to interface better and work as a reinforcement.…”
Section: Resultsmentioning
confidence: 98%
“…PCL sample shows a rough and compact surface, characteristic of tough materials while the inclusion of 0.1% wt of LWP induces a slight increase in roughness compared to the matrix, probably due to the presence of the nanometric pigment which in small quantities works as a concentrator of internal stresses. When the LWP content is increased to 1% wt, the surface becomes less jagged and the roughness decreases suggesting that LWP favors internal creep as a sort of plasticizer. , The fractured surface of PBS appears rough and segmented with the typical morphology of a rigid and tough material, whereas the PBS_0.1LWP sample takes on a less-wrinkled appearance, indicating a less tenacious behavior; with 1% wt of LWP in PBS, the fracture shows an evident reduction of the roughness, suggesting a more rigid and brittle behavior at break of the material. Unlike PCL-based samples, in PBS the pigment seems to interface better and work as a reinforcement.…”
Section: Resultsmentioning
confidence: 98%
“…It shifted from bright pink at pH 9 to vivid coral red at pH 10, orange at pH 11, and yellow from pH 12 to 14 (Amorim et al 2022c). In turn, flexirubin-type pigments are yellowish-orange pigments produced by various genera, including Flexibacter, Cytophaga, Sporocytophaga, and Chryseobacterium (Amorim et al 2022b). These pigments are recognized for their antioxidant and antimicrobial properties, as well as their appealing color in packaging that engages consumers' attention.…”
Section: Natural Colorantsmentioning
confidence: 98%
“…As previously mentioned, needleless electrospinning offers a significant advantage over traditional needle-based methods by providing a more efficient and scalable process. Amorim et al (2022b) and Amorim et al (2022d) reported the production of double-layer structures for active food packaging applications produced by needleless electrospinning (Amorim et al 2022b, d). In one of their works, double-layer materials were produced with an inner layer of nanofibers made from electrospun polyvinyl alcohol (PVA) and CH and an outer layer of oxidized BC to provide mechanical support.…”
Section: Natural Colorants In Polysaccharide-based Electrospun Food P...mentioning
confidence: 99%
“…In this regard, polymeric nanofibers incorporating flexirubin showed ABTS radical scavenging activity and the ability to reduce enzymatic browning of apple slices. Thus, the fabricated material has potential for application in active packaging systems [44]. Due to their properties, flexirubins have been proposed as useful dyes in textiles, food and pharma industries [6,36,40].…”
Section: Antioxidant Activitymentioning
confidence: 99%